THE ROLE OF THE JUDICIARY IN STRENGTHENING LEGAL AID CLINICS IN INDIA: AN EXAMINATION OF CASE LAWS, CHALLENGES, AND PATHWAYS TO JUSTICE (International Journal of Food and Nutritional Sciences, 2023)
The judiciary plays a vital role in ensuring access to justice for marginalized and vulnerable groups through legal aid clinics. Legal aid clinics are pivotal institutions that provide free legal assistance to individuals unable to afford private legal services. This paper explores how the judiciary has shaped and supported legal aid clinics through key judgments, policy frameworks, and judicial activism. It assesses the effectiveness of legal aid clinics, the challenges they face, and the need for judicial and legislative support to make these institutions more accessible, efficient, and effective. Through case law analysis and policy recommendations, this study offers insights into how judiciary-led interventions can further empower legal aid services and promote equitable access to justice for all.